2009
DOI: 10.1021/ja901655p
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acid (LNA)-Modified Dinucleotide mRNA Cap Analogue: Synthesis, Enzymatic Incorporation, and Utilization

Abstract: There has been considerable therapeutic interest in the development of human vaccines against cancers and infectious diseases such as HIV and biowarfare agents by using transfected mRNAs for antigenic proteins of interest. The highest expression levels of these proteins are obtained when the transfected mRNA contains 5'-capped ends. In the present study, the locked nucleic acid (LNA)-modified cap analogue 3, m(7(LNA))G[5']ppp[5']G, has been synthesized and its biological properties were examined. The LNA-modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 18 publications
(17 reference statements)
0
37
0
Order By: Relevance
“…These analogs are modified (or blocked) at the 3′- or 2′-OH hydroxyl of 7-methylguanosine to prevent recognition of this moiety by RNA polymerase [36, 101, 102]. The simplest and most commonly used modification is methylation of one of those groups, but ARCAs containing hydrogen (O–H substitution) or fluorine (O–F substitution) or even bulkier substituents have also been reported [37, 38, 103106]. Importantly, chemical modifications at these positions do not affect interactions with eIF4E or translation efficiency of such capped mRNAs, although, in the case of some bulkier substituents, the translation efficiency can be slightly decreased in comparison to ARCAs carrying simply a methyl group [37, 38].…”
Section: Chemically and Enzymatically Labeled Rna Capsmentioning
confidence: 99%
“…These analogs are modified (or blocked) at the 3′- or 2′-OH hydroxyl of 7-methylguanosine to prevent recognition of this moiety by RNA polymerase [36, 101, 102]. The simplest and most commonly used modification is methylation of one of those groups, but ARCAs containing hydrogen (O–H substitution) or fluorine (O–F substitution) or even bulkier substituents have also been reported [37, 38, 103106]. Importantly, chemical modifications at these positions do not affect interactions with eIF4E or translation efficiency of such capped mRNAs, although, in the case of some bulkier substituents, the translation efficiency can be slightly decreased in comparison to ARCAs carrying simply a methyl group [37, 38].…”
Section: Chemically and Enzymatically Labeled Rna Capsmentioning
confidence: 99%
“…Subsequently, it has been reported that 2 -OH modification on m 7 G moiety displays as an ARCA property. [12] Following these findings, several other ARCA-type modifications, such as 2 -fluoro, [13] 2 -araF, [14] LNA-m 7 G, [15] 2 -allyl, [16] and 2 ,3 -O,O-isopropylidene, [17,18] have been reported. It is noteworthy that these ARCA analogs outweighs standard cap analog in terms of their translational properties.…”
Section: Introductionmentioning
confidence: 75%
“…We envisaged that the introduction of acetyl group on both 2 and 3 -OH groups on m 7 G moiety would improve translational properties as well as intracellular stability due to the presence of bulky groups. Our continuous interest in the design of new cap analogs to improve the translational efficiency of capped mRNA, [13][14][15][16][17] prompted us to synthesize diacetyl cap analog and study its biological applications. Herein, we report the first example for the synthesis of cap analog containing 2 ,3 diacetyl group on m 7 G moiety such as m 7,2 ,3 -diacetyl G [5 ]ppp [5 ]G.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ever growing molecular biology applications, the development of a new and efficient gram-scale method for the preparation of aminopropargyl nucelotides with high purities would be highly valuable to meet the application of nucleic acid chemistry demand. Our continuous interest in the area of nucleic acid chemistry [20][21][22][23][24][25] prompted us to explore the possibility of palladium-catalyzed Sonogashira coupling reaction of 5-iodo-pyrimidine-5 -triphosphates with propargylamine for the synthesis of 5-aminopropargyl-pyrimidine-5 -triphosphates. In our preliminary communications, we reported the first example of highly regioselective iodination of uridine nucleotide [26] and also the first example of a palladiumcatalyzed Sonogashira coupling of 5-iodouridine triphosphates with propargylamine, leading to the formation of 5-aminopropargyl-uridine triphosphates in good yields with high purities.…”
Section: Introductionmentioning
confidence: 99%